Genetic overlap between executive functions and BMI in childhood. Issue 4 (19th June 2019) - Wood, Alexis C; Vainik, Uku; Engelhardt, Laura E; Briley, Daniel A; Grotzinger, Andrew D; Church, Jessica A; Harden, K Paige; Tucker-Drob, Elliot M
ABSTRACT: Background: Executive functions (EFs) comprise a group of cognitive processes that selectively control and regulate attention. Inverse relations have been reported between EFs and BMI. However, the mechanisms underlying this association are not well understood. Objectives: We aimed to decompose the inverse relation between EFs and BMI into genetic and environmental components. Methods: We employed a cross-sectional analysis of data from 869 twins aged 7–15 y from the Texas Twin Project, who completed a neuropsychological test battery measuring 4 EFs (switching, inhibitory control, working memory, and updating); academic achievement (reading and mathematics); and general cognitive abilities (general intelligence/intelligence quotient; crystallized and fluid intelligence; and processing speed). Participants also had their height and weight measured. Results: After controlling for age, sex, and race/ethnicity, BMI was inversely associated with a general EF factor representing the capacity to control and regulate goal-oriented behaviors ( r = −0.125; P = 0.01; Q = 0.04). This inverse BMI–EF association was due to a significant overlap in genetic factors contributing to each phenotype (genetic correlation, r A, = −0.15; P < 0.001). Shared genetic influences accounted for 80% of the phenotypic association. Conclusions: Children with higher general EF have lower BMIs, and this association is primarily attributable to shared genetic influences on both phenotypes. The results emphasize that higher weight associates not only with physical sequelae, but also with important cognitive attributes. This work adds to a growing body of research suggesting there are sets of genetic variants common across physical health and cognitive functioning.